Rachel Carson and her sisters : extraordinary women who have shaped America's environment - Musil, Robert K., 1943- (Rutgers University Press, 2014)
In Rachel Carson and her sisters, Robert K. Musil redefines the achievements and legacy of environmental pioneer and scientist Rachel Carson, linking her work to a wide network of American women activists and writers and introducing her to a new, contemporary audience. Rachel Carson was the first American to combine two longstanding, but separate strands of American environmentalism -- the love of nature and a concern for human health. Widely known for her 1962 best-seller, Silent spring, Carson is today often perceived as a solitary "great woman," whose work single-handedly launched a modern environmental movement. But as Musil demonstrates, Carson's life's work drew upon and was supported by already existing movements, many led by women, in conservation and public health